PENGEMBANGAN BAHAN AJAR KIMIA DENGAN MENGAITKAN NILAI-NILAI ISLAM MATERI HIDROKARBON KELAS XI SMA MUHAMMADIYAH 2 PONTIANAK - Fazira Nuratika; Rody Putra Sartika; Ira Lestari (EduChem, 2022)
This research is aimed to produce chemistry teaching material by connecting islamic values that was feasible to be used and to find out student’s responses to the product that developed. The form of the research was Research and Development (R & D)    with the ADDIE development model. The subject of this research is chemistry teaching material by connecting islamic values that was tested on  XI MIA class at SMA Muhammadiyah 2 Pontianak. Data collection instrument that was used were feasibility questionnaires and student responses questionnaires. The result showed that chemistry teaching material by connecting islamic values  was very valid for contents feasibility (91,42%), very valid for presentation feasibility (92%), valid for language feasibility (80%), and valid for islamic values feasibility (78,94%). The result of student’s responses showed that the chemistry teaching material has very high interpretations with total score of 81,88%. Thus, chemistry teaching material by connecting islamic values can be used as support in the learning process at school